PlayBionic: Game‐Based Interventions to Encourage Patient Engagement and Performance in Prosthetic Motor Rehabilitation. Issue 11 (1st November 2018) - Prahm, Cosima; Kayali, Fares; Sturma, Agnes; Aszmann, Oskar
Abstract: Background: Prosthetic motor rehabilitation usually relies on the highly repetitive training of movements. Patients might drop out of training because the rehabilitation process is long and often discouraging. Game‐based interventions provide a potentially useful alternative to standard myoelectric (electromyographic [EMG]) training and can increase engagement with training. Objective: To assess the short‐term impact of a game‐based rehabilitation protocol on parameters for EMG control, evaluate how game‐based interventions affect patient motivation, performance, and effort, and compare the game‐based intervention with a standard tool in rehabilitation (MyoBoy). Design: This randomized controlled trial included 2 patient groups and 1 control group. After establishing a baseline, the 2 patient groups received different interventions that were compared with each other and with the able‐bodied control group. Setting: University hospital‐based study. Participants: Fourteen patients with traumatic transradial or transhumeral upper extremity amputation and 10 able‐bodied participants. Methods: For the game‐based intervention, EMG proficiency was assessed before and after playing the games and 2 days later as follow‐up to measure retention rate. EMG proficiency was measured using maximum voluntary contraction, proportional precision control, signal separation, and muscle endurance. Questionnaires for rating the game‐based intervention and intrinsic motivation were provided after the intervention. Outcomes: Outcome measures for EMG proficiency were provisional maximum voluntary muscle contraction, precise proportional control, electrode separation, and muscle endurance. Quantitative outcome measures for participant experience were intrinsic motivation, enjoyment, pressure, exerted effort, and usefulness of the intervention. The qualitative outcome measure was the surveyed attitude toward the game‐based intervention. Results: Results showed an overall improvement in EMG control, fine muscle activation, and electrode separation. Patients stated that racing games provided slightly more fun, but rhythm‐based games were considered to provide better challenges for EMG control. Conclusion: Game‐based interventions provide a useful addition to standard EMG training and can achieve better results in clinical outcome measures. The racing and music game genres provide solid starting points for interventions. Further studies can look at a wider range of genres and identify more specific game mechanics suitable for training. Level of Evidence: I